Efektivitas Penggunaan Media Komik Digital untuk Meningkatkan Pemahaman Konsep Matematika Siswa MI/SD - Fina Alfiyatuzzahro; Chilmi Mazzatussyarifah; Laila Malihatussyarifah; Dian Mustika Anggraini (Educational Journal, 2026)
This study aims to determine the effectiveness of using digital comic media in improving mathematical concept understanding of third-grade students at MIN 2 Jepara on multiplication and division materials. This research employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest Design. The subjects consisted of 30 third-grade students of MIN 2 Jepara. Data were collected through tests, observations, and student response questionnaires. The results showed that the use of digital comic media positively contributed to students’ understanding of mathematical concepts. The average pretest score was 80 and increased to 95 in the posttest. Learning mastery reached 100%, with 20 students obtaining a score of 100, five students obtaining 90, and five students obtaining 80. Students also showed positive responses, indicating that digital comics made learning more enjoyable, engaging, and easier to understand because mathematical concepts were presented through stories and visual illustrations. The findings indicate that digital comic media can serve as an innovative learning medium that helps students understand abstract mathematical concepts more concretely. Therefore, digital comics can be used as an alternative learning medium to improve mathematics learning quality in elementary schools.